Weak NKX3.1 expression in a urothelial carcinoma: A diagnostic pitfall - Maryam Abdo; Robert Hoyt; Ashley Highfill; Daniel Mettman (Elsevier, 2022)
NKX3.1 is a reliable marker for identifying prostatic origin. While it is known to stain a number of other tissues, it has never been reported in a carcinoma of urothelial origin. We present the first case, to our knowledge, of a urothelial carcinoma with NKX3.1 immunohistochemical (IHC) staining. The lesion was centered on the right ureteral orifice in an 87-year-old male with a history of benign prostatic hyperplasia. We speculate on two potential explanations for the NKX3.1 staining. One possibility is that it arose from one of the previously described, rare NKX3.1-positive cells normally present throughout the ureter and bladder. Another possibility is based on the observation in mouse models that NKX3.1 expression increases in bladder urothelium in response to bladder outlet obstruction.